2019
DOI: 10.1001/jama.2019.18598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Strategy of Comprehensive Vasodilation vs Usual Care on Mortality and Heart Failure Rehospitalization Among Patients With Acute Heart Failure

Abstract: Short-term infusions of single vasodilators, usually given in a fixed dose, have not improved outcomes in patients with acute heart failure (AHF).OBJECTIVE To evaluate the effect of a strategy that emphasized early intensive and sustained vasodilation using individualized up-titrated doses of established vasodilators in patients with AHF. DESIGN, SETTING, AND PARTICIPANTSRandomized, open-label blinded-end-point trial enrolling 788 patients hospitalized for AHF with dyspnea, increased plasma concentrations of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 46 publications
4
95
0
2
Order By: Relevance
“…[62][63][64] Therefore, vasodilating agents should be used cautiously in normotensive patients with the risk of hypotension. 61,62,65 Furthermore, natriuretic peptide agents reduce the blood pressure more than nitrates, making them unsuitable as first-line vasodilators for normotensive patients with AHF. 32,62,65 Systemic congestion…”
Section: Vasodilatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…[62][63][64] Therefore, vasodilating agents should be used cautiously in normotensive patients with the risk of hypotension. 61,62,65 Furthermore, natriuretic peptide agents reduce the blood pressure more than nitrates, making them unsuitable as first-line vasodilators for normotensive patients with AHF. 32,62,65 Systemic congestion…”
Section: Vasodilatorsmentioning
confidence: 99%
“…Previous studies reported that early administration of vasodilators, even in the pre‐hospital setting, is associated with a lower morality risk in patients with pulmonary congestion 11,49,59 . Hence, recent clinical practice guidelines for HF have pragmatically recommended vasodilators as the first‐line medical therapy for patients presenting with pulmonary congestion, 7–9 despite no confirming evidence on their long‐term benefits associated with reduced mortality other than improved haemodynamics and dyspnoea 21,22,60,61 . However, hypotension may occur as an adverse effect of vasodilating agents and has been previously associated with unfavourable effects on morbidity and mortality, thereby limiting the beneficial vasodilatory effects 62–64 .…”
Section: Pulmonary Congestionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Contrary to significant advances in medical therapies for the treatment of chronic heart failure (HF), recent clinical trials of new ADHF therapeutics and treatment strategies have been negative. [7][8][9][10][11][12][13] Thus, loop diuretics remain the predominant therapy to treat fluid and sodium retention in ADHF and will remain so for the foreseeable future.…”
Section: Introductionmentioning
confidence: 99%
“…Ever-increasing burden of cancer becomes a major public health concern worldwide, posing a high impact on world health. Mortality due to cancer now exceeds the deaths caused by coronary heart diseases or all strokes [1]. International Agency of Research on Cancer (IARC) estimated 14.1 million new cancer incidences and 8.2 million cancer deaths worldwide in its online database GLOBOCAN 2012.…”
Section: Introductionmentioning
confidence: 99%